Novel Relative Permeability Modifier using Polymer Grafted Nanoclay - Abbas, Abdelazim (2020)
One of the major challenges in the upstream oil and gas industry is to control and reduce high water production from a large number of oil wells. A relative permeability modifier (RPM) has been proven to offer a potential solution for excessive water production at core and field scales. A good RPM must be of a cost-effective and simple agent that could easily be prepared in the field to control water production without requiring major workover equipment. This paper discusses the performance of a newly formulated grafted nanoclay (GN) for conformance control at high-temperature conditions and application as a permeability modifier. The interfacial tension (IFT) reduction and wettability change were quantified via pendant drop and contact angle measurements, respectively. Laboratory studies were performed using Berea and native sandstone cores to determine the effect GN on effective water and oil permeability. Experimental results obtained revealed that upon injection GN can immediately create a high flow resistance to the injected water. The regained water and oil permeability were 16% and 89%, respectively, after GN injection when the Berea core was used. A similar high resistance factor to water was obtained when a native core was used. Adsorption of GN on the substrate reduced the contact angle toward water-wetting combined with a reduction in IFT from 20.78 +/- 1.48 mN/m between an oil-brine system to 8.67 +/- 1.01 mN/m for an oil-GN system. These new results highlighted new insights for successful applications of GN to improve reservoir conformance in oil production wells.